MODERATING EFFECT OF MANAGERIAL OWNERSHIP ON THE RELATIONSHIP BETWEEN DIVIDEND POLICY, COMPANY GROWTH, AND COMPANY SIZE WITH DEBT POLICY DURING THE COVID-19 PANDEMIC - Margareta Beata Weti Liwu; Lin Oktris; Zubir Azhar (International Journal of Contemporary Accounting, 2024)
This study investigates the effect of dividend policy, company growth, and company size on debt policy, moderated by managerial ownership, during the COVID-19 pandemic. Using a purposive sampling technique, the research focuses on industrial, infrastructure, and technology companies listed on the Indonesia Stock Exchange in 2020 and 2021. The data analysis employs multiple regression analysis to explore these relationships. The results show that dividend policy and company growth have a positive effect on debt policy, while company size has no significant impact. Managerial ownership strengthens the positive effects of dividend policy and company growth on debt policy but does not significantly moderate the relationship between company size and debt policy. The novelty of this study lies in its focus on the industrial, infrastructure, and technology sectors during a global crisis, offering unique insights into sector-specific financial strategies in an emerging market. This research contributes to the literature by addressing the underexplored moderating role of managerial ownership on financial policies during times of uncertainty. The short observation period of 2020–2021 is a limitation, as it may not capture long-term trends. Future studies are encouraged to include post-pandemic data to provide a more comprehensive understanding of corporate financial strategies across different economic conditions. This study provides practical implications for enhancing corporate governance during crises. Strong managerial ownership can align managerial actions with shareholder interests, reinforcing financial policies and promoting resilience in times of economic uncertainty. These findings are especially relevant for investors and policymakers aiming to strengthen financial stability in emerging markets.